Hybrid-Identities: Degrees of Digital Selves - Boudreau, Kelly (AoIR Selected Papers of Internet Research, 2013)
Digitally mediated social network sites can be conceived as ‘sandbox games’ where users can play with and perform identity in a variety of ways. This paper will look at the ways in which Facebook and Pinterest offer two different platforms for identity play with both actual and idealized forms of selves through the posting and framing of personal information and the (re)appropriation of pre-existing content on the internet. In doing so, it will be demonstrated that it is possible for hybrid-identity to emerge and stabilize through the archival nature of the internet.